Outer wrapped concrete UHPC-stainless steel combined formwork air shaft structure and construction method - GE SHANMING; LIU GEJIA; ZUO KAIYUAN; YANG YONG; ZHANG SHUCHEN; LI HUAYU (2025)
The invention discloses an externally-wrapped concrete UHPC-stainless steel combined formwork air shaft structure and a construction method, the externally-wrapped concrete UHPC-stainless steel combined formwork air shaft structure comprises a UHPC-stainless steel combined formwork, staggered hole PBL shear keys, a reinforcement cage and external concrete, the UHPC-stainless steel combined formwork comprises a stainless steel cylinder and prefabricated UHPC, and the staggered hole PBL shear keys are arranged on the outer wall of the stainless steel cylinder. The performance advantages of a combined structure and an assembly type structure are combined, the rigidity and the bearing capacity of the UHPC-stainless steel combined formwork are enhanced, and the problems that a traditional stainless steel sheet is prone to deformation, bulging and protruding in the construction stage are effectively solved. Connection of the prefabricated UHPC, the stainless steel cylinder and external concrete is completed through